Ocupación ilegal de tierras y pérdida de cobertura vegetal urbana, caso estación de Pampachica - Iquitos. 2023 - Pezo Diaz, Daniela Rosario (2023)
The study explores the illegal occupation of land, the decisions on changes in land use by illegal occupants and the impact that is generated in the urban trees, the case of the illegal occupation of the land of the former Telefónica in the Pampachica area, San Juan Bautista District. The purpose of the investigation is to determine the impact of the illegal occupation of land on the loss of vegetation cover in the city of Iquitos. It is a quantitative, non-experimental, exploratory, descriptive, analytical, cross-sectional study. The primary information was obtained through the application of a structured interview that allows the development and analysis of the variables under study. It was determined that there was a 71.4 percent decrease in the existence of trees in the illegally occupied area; called "Pampachica Station", currently leaving 2 trees per plot, that is, 28.6 tree cover. This decrease in tree cover is mainly due to their felling to urbanize the area; Based on these data from the central tendency statistic, it is inferred that the illegal occupation of land has a negative impact on the vegetation cover in the city of Iquitos, for which the alternative hypothesis is accepted and the null hypothesis of the study is rejected.